2019
DOI: 10.1055/a-1023-4552
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eye Movement with PNF Neck Movement on Trunk Stability and Standing Position Balance Ability of Chronic Stroke Patients

Abstract: Objective We investigated the effects of eye movement with PNF neck movement on trunk stability and standing position balance ability of chronic stroke patients. Methods A total of 30 patients were randomly divided into EMPN group and CON group. EMPN group was performed 60 min three times a week for 8 weeks in eye movement and PNF neck movement. CON group performed conservative treatment for 60min. The trunk stability was measured by the Trunk impairment scale (TIS) and the standing balance ability test was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…Following deduplication, 518 articles underwent title and abstract screening. In the end, 68 articles were included for full-text review, which further excluded 49 articles, with the remaining 19 studies for qualitative synthesis [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Screening the evaluation instruments used showed that the Berg balance scale (BBS), functional reach test (FRT), timed up-and-go test (TUG) and 10-m walking test (10MWT) were used in at least three separate studies, and their data in a total of 12 articles were combined for quantitative review by meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Following deduplication, 518 articles underwent title and abstract screening. In the end, 68 articles were included for full-text review, which further excluded 49 articles, with the remaining 19 studies for qualitative synthesis [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Screening the evaluation instruments used showed that the Berg balance scale (BBS), functional reach test (FRT), timed up-and-go test (TUG) and 10-m walking test (10MWT) were used in at least three separate studies, and their data in a total of 12 articles were combined for quantitative review by meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…All studies selected patients with chronic stroke who had been diagnosed with stroke at least six months earlier as a primary inclusion criteria. Of the nineteen studies analyzed, fifteen studies used stroke at the chronic stage for those who could understand and follow the researcher′s instructions according to Mini-Mental State Examination scores (MMSE > 20 points) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 30 , 31 , 34 , 35 , 36 , 39 ]. Two studies used the Brunnstrom scale [ 35 , 37 ] and three studies used the Modified Ashworth Scale (MAS) [ 25 , 31 , 38 ] to describe the spastic and involuntary muscle movement of lower limbs as inclusion criteria of a participant’s motor severity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations